Analysis of the acceptability of the "information health" concept: Consideration of the possibility of beneficiary payment - Teppei Koguchi; Toshiya Jitsuzumi (International Telecommunications Society (ITS), 2023)
The current information platform is under the negative effects of the attention economies such as filter bubble, echo chamber and so on. These problems inhibit individuals from properly understanding information on the Internet and cause individuals to make incorrect decisions. Digital platforms and SNSs, the actors that control information on the Internet, are dealing with these issues on their own initiative, but have yet to reach a drastic solution. The 2021 United States Capitol attack, in which social networking sites were noted to have had a major impact, is fresh in our memories. Even if this is not such an extreme case, we are often deceived by fake news or exposed to biased information in our daily lives.
Keywords: 330